2010
DOI: 10.1007/s11144-009-0140-z
|View full text |Cite
|
Sign up to set email alerts
|

Study of SBA-15 supported catalysts for toluene and NO removal: the effect of promoters (Co, Ni, Mn, Ce)

Abstract: SBA-15 materials were synthesized through the hydrothermal method. The SBA-15 prepared at the hydrothermal time of 24 h possessed a higher surface area and a good hexagonal structure, so it was used as the catalytic support in this experiment. The base metals (Cu, Co, Ni) coated on SBA-15 were prepared for toluene removal. The results revealed that the catalytic activity of Cu/SBA-15 for toluene removal was about 70% at 250 degrees C, which was the best among the three catalysts. The modification of Cu/SBA-15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…It was preliminary proposed that the NiO–CuO NPs are stabilized by a confinement effect of the micro/mesoporous structure of SBA-15 and by strong Ni–Cu and Ni–silica interactions, yet in-depth investigations are compulsory to shed more light. From a broader and practical perspective, the scientific interest in supported bimetallic Ni–Cu NPs also arises because of their enhanced catalytic activity and/or selectivity relative to single-component catalysts, as shown in a wide variety of chemical reactions such as hydrocarbon steam reforming, , NO x reduction, CO hydrogenation, methane partial oxidation, , water gas shift, glycerol hydrogenolysis, hydrogenation of aromatics, as well as chemoselective hydrogenation of α,β-unsaturated aldehydes. The catalytic properties of bimetallic Ni–Cu NPs were usually associated with the synergistic effects between Ni and Cu atoms (i.e., geometric and/or electronic effects), as already proposed in the early literature. , …”
Section: Introductionmentioning
confidence: 99%
“…It was preliminary proposed that the NiO–CuO NPs are stabilized by a confinement effect of the micro/mesoporous structure of SBA-15 and by strong Ni–Cu and Ni–silica interactions, yet in-depth investigations are compulsory to shed more light. From a broader and practical perspective, the scientific interest in supported bimetallic Ni–Cu NPs also arises because of their enhanced catalytic activity and/or selectivity relative to single-component catalysts, as shown in a wide variety of chemical reactions such as hydrocarbon steam reforming, , NO x reduction, CO hydrogenation, methane partial oxidation, , water gas shift, glycerol hydrogenolysis, hydrogenation of aromatics, as well as chemoselective hydrogenation of α,β-unsaturated aldehydes. The catalytic properties of bimetallic Ni–Cu NPs were usually associated with the synergistic effects between Ni and Cu atoms (i.e., geometric and/or electronic effects), as already proposed in the early literature. , …”
Section: Introductionmentioning
confidence: 99%
“…29,30,36,42 However, the effect of thermal conditions during calcination and reduction on the dispersion and stability of oxidic and catalytic metallic phases has not been specifically investigated. On the other hand, it has been reported that, even at metal loadings lower than 5 wt.%, the oxide particles are irregularly dispersed throughout the support channels or located on the external surfaces, 29,42 suggesting severe redistribution and sintering phenomena during calcination. Herein, we report a simple approach to confine copper-nickel NPs in the channels of ordered mesoporous SBA-15, which involves the IWI method and drying of the metal precursors at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to the monometallic catalysts, a more complex situation could arise during the different steps of IWI preparation (referred as co-impregnation), due to different affinities of the precursors for the support surface, possibility of synergic interaction between metals and interdiffusion phenomena, alloy formation, surface segregation of one metal etc. Particularly, supported bimetallic CuNi NPs have attracted considerable attention recently due to their enhanced activity and/or selectivity and stability, as compared to the monometallic counterparts, in various applications such as ethanol steam reforming, [29][30][31] methane decomposition, 32,33 methane steam reforming, 34 methane dry reforming, 35 methane and methanol partial oxidation, 36,37 methanol decomposition, 38 CO and CO 2 hydrogenation, 39,40 NO x reduction, 41,42 water gas shift, 43 hydrogenation of a,bunsaturated aldehydes [44][45][46] and so on. It was suggested that the improved catalytic performances are induced by Cu addition to Ni which causes changes of the geometric and/or electronic properties of Ni in the bimetallic alloy particles (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the above metal oxides are considered in the order of effectiveness for VOCs. Compared to others, cerium and 2 of 15 manganese oxides exhibited better catalytic activities at low temperatures in previous research [6][7][8][9]. Furthermore, both CeO 2 and MnO X have abundant valence changes of metal cations, surface defect sites and reactive oxygen species, which exhibit excellent electron transfer ability and make them potential catalysts [10][11][12].…”
Section: Introductionmentioning
confidence: 86%